Association of habitual glucosamine use with risk of microvascular complications among individuals with type 2 diabetes: a prospective cohort study in UK biobank - Zi-Jian Cheng; Yu-feng Luo; Qing-yun Zhu; Yan-fei Wang; Wen-yan Ren; Fei-yan Deng; Lin Bo; Xi-Yuan Jiang; Shu-feng Lei; Long-Fei Wu (Nutrition & Diabetes)
Abstract Background Glucosamine is a widely used supplement for treating osteoarthritis and joint pain. New evidence suggests a potential association between glucosamine and type 2 diabetes, inflammation and cardiometabolic risk. We aimed to prospectively evaluate the association of habitual glucosamine use with risk of diabetic microvascular complications based on data from the large-scale nationwide prospective UK Biobank cohort study. Methods This analysis included 21,171 participants with type 2 diabetes who were free of microvascular complications from the UK Biobank. Incidence of diabetic microvascular complications was ascertained via electronic health records. The Cox proportional hazards model was used to assess the relationship between glucosamine use and the risk of diabetic microvascular complications. Subgroup analyses and sensitivity analyses were performed to explore the potential effect modifications and the robustness of the main findings. Results At baseline, 14.5% of the participants reported habitual use of glucosamine supplements. During a median follow-up of 12.3 years, 4399 people developed diabetic microvascular complications, including 2084 cases of incident diabetic nephropathy, 2401 incident diabetic retinopathy, and 831 incident diabetic neuropathy. Glucosamine use was significantly associated with lower risks of composite microvascular complications (hazard ratio (HR) 0.89, 95% CI: 0.81 to 0.97) and diabetic nephropathy (HR 0.87, 95% CI: 0.76 to 0.98) in fully adjusted models. However, there was no significant inverse association between glucosamine use and the risk of diabetic retinopathy (HR 0.94, 95% CI: 0.83 to 1.06) or diabetic neuropathy (HR 0.88, 95% CI: 0.71 to 1.08). Conclusions Habitual use of glucosamine supplement was significantly associated with lower risks of composite microvascular complications and diabetic nephropathy but not retinopathy or neuropathy in individuals with type 2 diabetes.